Activation of phenylalanine ammonia lyase contributes to non-host resistance in Triticum aestivum against Scierotinia scierotiorum - S.C. CHATTERJEE, S. AMEER BASHA* and (Indian Phytopathology, 2007)
Foliar application of plant growth-promoting rhizobacterial (PGPR) strains, viz., Pseudomonas fluorescens (Pf4) and P. aeruginosa (Pag) , and two non-conventional chemicals zinc sulphate (10 ~ mM) and oxalic acid (4 mM) induced synthesis of phenylalanine ammonia lyase (PAL) in wheat (Triticum aestivum). Increased PAL activity followed by accumulation of different phenolic acids demonstrated that activation of the phenylpropanoid pathway is one of the reasons for resistance in wheat against Sclerotinia sclerotiorum and thereby serves as a non-host. Sensityvity of S. sclerotiorum towards the individual phenolic acids (tannic, gallic, ferulic, vanillic and cinnamic acids) further supports the role of activation of the phenylpropanoid pathway as one of the reasons for non-susceptibility of wheat to S. sclerotiorum. This phenomenon of induction of resistance by activation of the phenylpropanoid pathway may be exploited to induce resistance in the hosts of S. sclerotiorum by the biotic and abiotic agents used uin the present investigation. The experiment also convincingly demonstrated that inducible antimicrobial are also responsible of becoming a plant non-host to a pathogen of other hosts.